Rhodium(III)-Catalyzed C–H Activation: Annulation of Petrochemical Feedstocks for the Construction of Isoquinolone Scaffolds - Barber, Joyann S.; Kong, Dehuan; Li, Wei; McAlpine, Indrawan J.; Nair, Sajiv K.; Sakata, Sylvie K.; Sun, Nicole; Patman, Ryan L. (Synlett, 2021)
We describe a simple and robust procedure for the Rh(III)-catalyzed [4+2] cycloaddition of feedstock gases enabled through C–H activation. A diverse set of 3,4-dihydroisoquinolones and 3-methylisoquinolones have been prepared in good to excellent yields. The effects of using ethylene and propyne as coupling partners on C–H site selectivity have also been explored with a representative set of substrates and are discussed herein.
Keywords: heterocycle synthesis; medicinal chemistry; rhodium catalysis; C–H activation; C–C bond formation; isoquinolone; feedstocks; annulation